Pengaruh Pemahaman Akuntansi dan Pemahaman Perpajakan Terhadap Kepatuhan Wajib Pajak Usaha Hits Dimsum Surabaya - Asri, Sukma; Hwihanus (Teewan Journal Solutions, 2025)
This study aims to analyze the effect of accounting and taxation understanding on tax compliance in small businesses Hits Dimsum Surabaya. The research method used is a case study with data collection through in-depth interviews, participatory observation to assess accounting understanding and taxation understanding affect tax compliance. The results showed that although the owners have a basic understanding of financial recording and the importance of profit and loss statements, the application of this knowledge in terms of taxation is still very limited. In addition, ignorance of tax obligations also reduces their level of compliance. This shows that accounting understanding and understanding of taxation have a significant influence on taxpayer compliance in the Hits Dimsum Surabaya business. The advice given is to carry out taxation counseling and accounting training that is more specific to MSME actors, and improve access to training programs. In addition, the importance of simpler and more transparent tax policies is expected to help business owners understand their tax obligations and realize the benefits of tax compliance.